2010
DOI: 10.4103/0973-1296.66942
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of alantolactone and isoalantolactone from Inula helenium roots

Abstract: This work deals with ultrasound-assisted extraction (UAE) of alantolactone and isoalantolactone from the roots of Inula helenium L., a well-known medicinal plant. The effects of ethanol concentration, extraction time, temperature and number of extraction steps on the extraction yields of both sesquiterpene lactones were investigated. Gas chromatographic (GC) method was used for simultaneous determination of their contents in the corresponding extracts. A comparison with classical extraction methods [maceration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 9 publications
3
31
0
Order By: Relevance
“…Recently, UAE had been widely for extraction of sesquiterpene,[5] flavonoids,[6] phenolics,[7] and polysaccharide,[8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, UAE had been widely for extraction of sesquiterpene,[5] flavonoids,[6] phenolics,[7] and polysaccharide,[8] etc.…”
Section: Introductionmentioning
confidence: 99%
“…EASP extract was mainly composed of an enhances solvent penetration through plant cell with the aid of sound wave. 9 Its mechanistic action includes fragmentation, erosion, and destruction-detexturation of plant structures, thus, this will enhance the diffusion process by increasing the solute transfer rate. 10,11 This method is usually employed for its higher extraction efficiency and its shorter extraction time as compared to maceration and soaking with the less amount of solvent application.…”
Section: Gc-ms Analysis For Ethyl Acetate Extract Of S Polyanthum Lementioning
confidence: 99%
“…10,11 This method is usually employed for its higher extraction efficiency and its shorter extraction time as compared to maceration and soaking with the less amount of solvent application. 9,10 Recently, UAE method was applied in many researches to enhance extractability of phenolic, thermo-labile and unstable compounds. 12,13 A recent study by Ramli et al 13 has utilized this method for extraction of S. polyanthum leaves, and has proven that the extract possess significant renal protective effect in Spontaneously Hypertensive Rats.…”
Section: Gc-ms Analysis For Ethyl Acetate Extract Of S Polyanthum Lementioning
confidence: 99%
“…Alantolactone is a traditional Chinese medicinal herb officially listed in pharmacopeias (Stojakowska et al, 2006;Trendafilova et al, 2010). It belongs to a sesquiterpene lactone, and mainly extracted from the roots of I. helenium L. Alantolactone possesses an inhibitory activity for inflammation, microbial and cell growth in several cancer cell lines (Konishi et al, 2002;Lawrence et al, 2001) as reported before.…”
Section: Discussionmentioning
confidence: 82%